3‐D Coupled Analysis of Deformation of the Strip and Rolls in Flat Rolling by FEM. Issue 12 (4th October 2017) - Park, Hyojin; Hwang, Sangmoo
Abstract : In flat rolling mills, while demands for precise process set‐up and control are increasing than ever before, it is difficult to improve the prediction accuracy of the existing models to the level of satisfaction. This seems particularly true for the models for the prediction of the strip profile. The breakthrough may be achieved, if new models are to be developed on the basis of powerful and rigorous finite element simulation capabilities. In this paper, the authors present a rigorous finite element (FE) approach for 3‐D coupled analysis of the elastic‐plastic deformation of the strip and the elastic deformation of rolls in the roll‐stack of a mill stand. FE formulations, strategies for the treatment of the 3‐D coupled nature of the problem, and the related computational schemes are described in detail, with some examples and illustrations. The prediction accuracy of the proposed approach is also examined through comparison with measurements. Abstract : A general approach is proposed for 3‐D coupled FE analysis of the deformation of the strip and rolls in flat rolling. FE formulation, schemes for the treatment of contact occurring in a cluster of deforming objects, and the solution strategy are described in detail. The validity of the approach is examined through comparison with measurements. The approach is applied to the analysis of deformation occurring in a four‐high mill and also in a six‐high mill.